Formulasi Sediaan Gel Antibakteri Dari Ekstrak Biji Kopi Robusta (Coffea Canephora L.) Sebagai pengobatan luka diabetes - Jesika Nopa Yanti Br. Nainggolan; Novitaria Br. Sembiring; Vera Estefania Kaban (Journal of Pharmaceutical and Sciences, 2026)
Diabetic wounds are chronic wounds that are susceptible to bacterial infection and therefore require optimal therapy. Robusta coffee beans (Coffea Canephora L.) are known to contain various active compounds, including polyphenols, alkaloids, and flavonoids, which have antibacterial potential. This study aimed to develop a gel preparation based on Robusta coffee bean extract and to assess its antibacterial activity against Staphylococcus epidermidis and its physical properties. The extract was obtained through a maceration process using 96% ethanol and then formulated into three concentration variations: F1 (30%), F2 (50%), and F3 (75%). The tests included phytochemical screening, organoleptic evaluation, homogeneity, pH, spreadability, and antibacterial activity testing using the disc diffusion method. The screening results indicated the presence of flavonoids, alkaloids, tannins, and terpenoids in the extract. All gel formulations had good physical properties, with a pH ranging from 5.42 to 6.33 and a spreadability of 5.0 to 6.7 cm. Antibacterial activity increased with increasing extract concentration, indicated by the inhibition zone diameters of 11.98 mm (F1), 17.76 mm (F2), and 18.49 mm (F3), respectively. Thus, the Robusta coffee bean extract gel preparation meets the topical physical requirements and has the potential to be used as an alternative therapy for diabetic wounds.